Utilization of Plants in Postpartum Maternal Care in Watulea Village, Central Buton Regency - Hasriani; S. Hafidhawatii Andarias; Agus Slamet (Jurnal Biologi Tropis, 2023)
The fact is that some people have giving birth medically, but postpartum care is still done traditionally. The treatment used concoctions of various types of plants. This study aims to preserve traditional knowledge through documenting community knowledge regarding postnatal care using plants by traditional methods in Watulea Village, Central Buton. The selection of respondents was carried out by purposive sampling technique. Data related to goals was collected by semi-structured interviews with 3 healers and 11 women who had used plants in postpartum care. Data from the interviews were the plant information such as local names, parts of the plants used, and descriptions of the traditional use of plants, including how to prepare and utilization. Data processing is done by descriptive analysis and presented in the form of tables and narratives. The result show that 23 species, belonging to 16 families which were used either singly or a mixture of various plants in the form of 3 types concoction, namely ramuan minum, ramuan mandi, and ramuan balur. Even though the plant compounds used have not been fully scientifically proven regarding the intended properties although it is proven that some of the ingredients used in these ingredients contain substances that are beneficial to the body-, their use has been going on for generations because of the positive impact felt directly by consumers.